First-Year Students’ Self-Efficacy in Basic Writing - Yunika Upa; Concilianus Laos Mbato; Efrika Siboro; Mustika Aji Hertanto; Ninyikiriza Deborah Lynn (Lembaga Pendidikan Hikmatun Najah Blora, 2025)
First semester students face a transition period as an adaptation process to prepare themselves for changes in the academic environment. Students who have difficulty adjusting to changes and new academic demands tend to feel stressed and face various conflicts in meeting the demands of the academic environment. Self-efficacy is students' belief in their own abilities, playing an important role in determining their success in facing academic demands. The objective of this study was to investigate the role of self-efficacy in basic writing of first year students in English Language Education Study Program. The researchers gained data from 26 students in Basic writing Class by using quantitative approach. From the data analysis the researchers found that the self-efficacy of first-year students was considered good even though it was still low, with an average self-efficacy of 3.9. This shows that self-efficacy needs to be considered as a key factor that influences the process and results of student learning. Therefore, it is important for educators to explain to students about the role of self-efficacy in supporting their success in learning, as well as provide support to increase students' self-confidence in their ability to learn and write.